Narrative Transvestism Rhetoric and Gender in the Eighteenth-Century English Novel - Kahn, Madeleine (Cornell University Press, 2018)
Many of the earliest canonical novels—including Defoe's Moll Flanders and Roxana and Richardson's Pamela and Clarissa—were written by men who assumed the first-person narrative voice of women. What does it mean for a man to write his "autobiography" as if he were a woman? What did early novelists have to gain from it, in a period when woman's realm was devalued and woman's voice rarely heard in public? How does the male author behind the voice reveal himself to readers, and how do our glimpses of him affect our experience of the novel? Does it matter if the woman he has created is believable as a woman? Why does "she" inevitably rail against the perfidy of men?Kahn maintains that the answers to such questions lie in the nature of "narrative transvestism" -her term for the device through which a male author directs the reader's interpretation by temporarily abandoning himself to a culturally defined female voice and sensibility and then reasserting his male voice.In her innovative readings of key eighteenth-century English novels, Kahn draws upon a range of contemporary critical approaches. Lucid and witty, Narrative Transvestism will serve as a model of analysis for readers interested in issues of gender in narrative, including feminist theorists, students and scholars of the eighteenth-century novel, and critics interested in the applications of psychoanalysis to literature
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mrz 2019)
Keywords: Richardson, Samuel -- 1689-1761 -- Clarissa; Defoe, Daniel -- 1661-1731 -- The fortunate mistress; LITERARY CRITICISM / Subjects & Themes / Women; First person narrative; Narration (Rhetoric) -- History -- 18th century; Sex role in literature; Women in literature; Crossdressing -- Motiv; Crossdressing